MILLENIAL INVESTMENT DI KOTA MEDAN - NUR NAFISAH; ELLA ARISKA (LP2MTBM MAKARIOZ, 2022)
Investment is an activity to invest in a fairly long period of time with the hope of obtaining profits in the future or in the future. Currently, the profile of stock investors on the IDX is dominated by young investors. This study aims to find out what investments are chosen by the millennial generation in the city of Medan. This study uses a qualitative research method with a phenomenological approach. The results show that the millennial generation of Medan City prefers to invest in gold then stocks.